Boarfish ( Capros aper ) in subareas 6–8 (Celtic Seas, English Channel, and Bay of Biscay) ... - ICES (ICES Advice: Recurrent Advice, 2023)
ICES advises that when the MSY approach is applied, catches should be no more than 27 349 tonnes in each of the years 2024 and 2025. ...